A teaching proposal of historical time for teacher training in the Argentine public university - Sayago Gorosito, Rocío Ana Esperanza (2023)
This paper presents and reflects on a teaching proposal for the initial training of History teachers designed in a public university in Argentina, which has historical time as its axis and which is part of a final postgraduate project, of the University of Córdoba, Faculty of Philosophy and Humanities, defended this year. The theoretical framework that supports it and the design of the didactic sequence itself, designed for future colleagues in training, are presented. Next, we ask ourselves about its relevance, in a new epochal context, such as the post-pandemic, based on the following questions: what temporal categories are essential to learn in initial teacher training, so that later their students are able to understand and interpret the current world and make decisions accordingly?; In times of immediacy and uncertainty, what relevance do present-future relationships have in teacher training and in secondary level classrooms, in which most future teachers will have to work?It is assumed that this article will be a contribution to the training of teachers, at the higher level, and also to other colleagues in Social Sciences, interested in the problem of historical time in school.